OPTIMIZATION OF CAPILLARY PIPE DIAMETER FOR THE PERFORMANCE OF A 100-LITER CAPACITY ICE PLANT AS A MEANS OF PRESERVING FISH - Tupamahu, Cendy; Salamor, Axel; Nuha, Widyastutifajri (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
The capillary tube is an expansion device in the vapor compression refrigeration cycle (VCRC) that functions to reduce refrigerant pressure from high to low levels. The tube’s diameter and length significantly affect the pressure and performance of the refrigeration system. Therefore, selecting the appropriate capillary tube size is essential to achieve optimal system operation. This study aims to determine the optimal capillary tube diameter to improve the performance of a 100 liter ice maker unit utilizing a 1 PK air conditioner outdoor unit as the condensing unit. The system is designed to support an efficient and simple ice freezing process for fish preservation. The main variable analyzed is the capillary tube diameter (0.028 inch, 0.031 inch, and 0.040 inch). Evaluation parameters include refrigeration effect (Qc), compressor work (Wk), condenser heat rejection (Qk), and coefficient of performance (COP). The results indicate that a 0.028-inch capillary tube yields a refrigeration effect of 345.35 kJ/kg, compressor work of 78.26 kJ/kg, and a COP of 3.41. The 0.031-inch and 0.040-inch diameters result in COP values of 3.31 and 3.29, respectively. Therefore, the 0.028-inch capillary tube provides the highest performance and is considered the most suitable for the 100 liter ice maker system.